Implementasi QR Untuk Legalitas Tanda Tangan Digital di Lingkungan STMIK Bandung - Indra Maulana Yusup Kusumah; Efrizal Fikri Yusmanyah; Meidi Fransisca Siregar; Puput Fatmawati (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2024)
The use of electronic documents and academic letters raises problems regarding the validity of digital signatures and document security. This research introduces a solution by applying QR Code technology for the legality of digital signatures in the STMIK Bandung environment. Problems identified include the absence of a digital signature verification system, a manual signing process, and the risk of signatures being duplicated and manipulated. This research focuses on designing and implementing a signature verification system using QR Code technology. The main goal is to create a system that can verify the authenticity of signatures on documents and letters using QR Codes. This system provides a unique QR Code for each person and document, minimizing the risk of signatures being copied and duplicated. The result of this research is the implementation of a digital signature verification system using QR Code which can increase security, efficiency, accuracy and productivity in managing academic documents and letters at STMIK Bandung.